The Potential of Otherness in Robotic Art - Sandry, Eleanor (Springer, 2016)
This chapter compares and contrasts the creation of humanoid robots with that of non-humanoid robots, identifying assumptions about communication that underlie the designs and employing a range of communication theories to analyse people's interactions with the robots. While robots created in science and technologies laboratories to communicate with humans are most often at least somewhat humanlike in form, those created as part of interactive art installations take a variety of forms. The creation of humanoid robots can be linked with ideas about communication that valorise commonality above all else, whereas robotic artworks illustrate the potential of otherness in interactions between humans and non-humanoid robots.